An updated review on the diagnosis and treatment of nocturia in Parkinson’s disease - Sarah Nonglaton; Thomas Gabriel Schreiner (Romanian Journal of Neurology)
Background and objectives. In recent years, neurologists have increasingly focused on the non-motor symptoms of Parkinson's disease, given their significant impact on patients' quality of life. Among these symptoms, nocturia is a common autonomic disturbance. With new insights emerging on its diagnosis and treatment, an updated review of nocturia in Parkinson's disease is essential. Materials and methods. This narrative review is the result of a thorough search in the most important electronic databases (PubMed, Google Scholar, Embase, and Science Direct) for articles published in the English language starting from 1 January 2015 involving human subjects on the topic of nocturia in Parkinson’s disease, focusing on the diagnosis and therapeutic approaches. Results. This section can be divided into three parts, showing the natural flow of understanding, diagnosing, and managing nocturia in Parkinson’s disease. While initially, the most relevant pathophysiological mechanisms are reviewed in detail, the authors offer a diagnosis workflow to facilitate the detection of nocturia among Parkinson’s disease patients. Finally, several strategies for resolving nocturia and other lower urinary tract symptoms are highlighted. Conclusions. Nocturia remains a crucial non-motor symptom in Parkinson’s disease, having a significant negative impact on the patient’s quality of life. Based on current knowledge, the diagnosis of nocturia should be easier and faster, ensuring the use of appropriate treatment options.